2020
DOI: 10.1021/acssensors.0c00014
|View full text |Cite
|
Sign up to set email alerts
|

Crucial Role of Out-of-Pore Resistance on Temporal Response of Ionic Current in Nanopore Sensors

Abstract: We investigated the temporal resolution of ionic current in solid-state nanopore sensors. Resistive pulses observed upon translocation of single-nanoparticles were found to become blunter as we imposed larger external resistance in series to the pore via the integrated microfluidic channels on the membrane. This was found to occur even when the out-of-pore resistance is more than an order of magnitude smaller than that at the nanopore, which can be understood as a predominant contribution of charging/dischargi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…The relationship as a whole implied the direct relevance of the time-varying R ele to the temporal resolution of nanopore sensors (note that τ 1 scales linearly with R even within the data acquired under a certain salt concentration condition). In this context, it is noticeable that similar trends were reported when varying solution resistance at external regions of nanopores by integrating microchannels on membranes ( Kishimoto et al., 2020 ). The τ 1 – R dependence thus indicates the major contribution of R ele to alter the out-of-pore resistance contributing to the signal retardation.…”
Section: Resultssupporting
confidence: 65%
“…The relationship as a whole implied the direct relevance of the time-varying R ele to the temporal resolution of nanopore sensors (note that τ 1 scales linearly with R even within the data acquired under a certain salt concentration condition). In this context, it is noticeable that similar trends were reported when varying solution resistance at external regions of nanopores by integrating microchannels on membranes ( Kishimoto et al., 2020 ). The τ 1 – R dependence thus indicates the major contribution of R ele to alter the out-of-pore resistance contributing to the signal retardation.…”
Section: Resultssupporting
confidence: 65%
“…However, in resistive pulse sensing, the charging/discharging of stray capacitance belonging to the device may retard the current signal and hinder accurate analysis of the temporal response of the ionic current due to the fast translocation of the analyte . In addition, a recent report has demonstrated that resistance outside a pore significantly affects signal retardation . Therefore, careful treatment of signal analysis is needed.…”
Section: Nanopore Sensingmentioning
confidence: 99%
“…44 In addition, a recent report has demonstrated that resistance outside a pore significantly affects signal retardation. 45 Therefore, careful treatment of signal analysis is needed.…”
Section: ■ Nanopore Sensingmentioning
confidence: 99%
“…(1) A small interior volume as well as a small dead volume is necessary to generate a rapid gas response under the lower gas sample consumption and gas residue. (2) The cross section of the microchannel should have a similar geometry size to the GC column to provide a smooth interface of the gas flow. (3) The smooth gas flow in the microchannel should be laminar to avoid the remixing of analytes.…”
Section: ■ Designing and Modelingmentioning
confidence: 99%
“…The ionic current extracted from the ionized gas molecule under the energy source has been widely used in electronic devices. Gas sensing is one of the applicable fields, where the ionic current containing the analyte information is demonstrated to be sensitive to the gas species and the concentrations. , Some ionization-based detectors in the literature have been summarized in Table S1 of the Supporting Information. Typically, the ions generated by the photon source and the hydrogen flame , can be extracted by a collection electrode as the ionic current for gas detection in the photon ionization detector (PID) and flame ionization detector (FID) of gas chromatography (GC), respectively.…”
mentioning
confidence: 99%